Nursing shortage and management: Personal Level Management - Yodtong, Dusanee (Journal of Nursing, Siam University, 2019)
Abstract Shortage of nurses is a national problem that has accumulated for a long time. Management to solve problems often focus on external factors such as progression, compensation, justice, the environment in the workplace, etc. This article presents a solution that has not yet been seriously discussed. It focuses on the internal factors of the personnel, such as attitudes appropriate to the profession, self-esteem and the value of the work. It will be seen that obtaining personnel who are unfit to work and have no love in the nursing profession is a terrible experience of the organization. They come into the profession because of the influence of their family. And there is no way to think in the same direction with corporate culture and values, those people will not be able to work in the organization long enough. Recruiting candidates with professional attitudes prior to admission is the process of casting personnel to achieve a good attitude, suitable for the organization. It’s going to be more effective. In addition, the promotion of self-esteem and job value is serious and systematic. It is the power to motivate people to work in love, to enjoy to work, to contribute to the quality and efficiency and be proud of the success. Those people will make love commitment to the organization and will remain in the organization for a long time, effecting on the achievement of the goals, the development of the ability of the organization to change and the needs of society and the nation.